In Vitro Comparative Study of Antioxidant and Antibacterial Activity of Selected Dietary Plants - Kumar, Ashok; Sharma, Palvi; Mahajan, Anupama; Begum, Zarina (Nepal Journal of Biotechnology, 2019)
Ethanolic extracts of Garlic (Bulb), Aloe (leaf), Flower bud (buds), Turmeric (rhizomes) and Ginger (rhizomes) were used for relative analysis of antioxidant and antimicrobial activity. Antioxidant activity was determined by DPPH [1, 1-Diphenyl-2-picryl hydrazyl] assay and expressed with Ascorbic acid. It was observed that turmeric and ginger have more antioxidant activity than garlic, Aloe and Flower bud. These extracts were further studied for antibacterial activity by agar well diffusion and spectrophotometric method against tetracycline as reference. The result showed that Flower bud is more effective against Escherichia coli, Pseudomonas aeuroginosa, Bacillus subtilis and Staphylococcus aureus compared to other plants extract. However, all the plants extract did show antioxidant and antibacterial activity.